Surgical correction of severe enophthalmos caused by bullet injury - S M Balaji (Wolters Kluwer Medknow Publications, 2016)
Ballistic injuries of oral and maxillofacial region are usually fatal due to close propinquity with the vital structures. The severity of injury depends on the caliber of the weapon used and distance from which the patient is shot. The preliminary care of facial ballistic wounds strictly adheres to the basics of trauma resuscitation. Early and appropriate surgical management has proved to be influential on the final outcome and esthetic result. Treatment of facial gunshot wounds should be planned and carried out carefully to avoid esthetic complications. It takes even multiple-staged corrections to achieve the targeted functional and esthetic treatment plan. Prevention and control of infection is one of the most important goals to achieve the success of the treatment. Herewith, we present a case of facial gunshot injury with fractures in the orbital floor, medial wall maxillary sinus, and buttress of the zygomatic bone causing deficit, which was successfully managed by surgical reconstruction.